Gamification: What it is, and how to fight it - Woodcock, J; Johnson, MR (SAGE Publications, 2017)
‘Gamification’ is understood as the application of game systems – competition, rewards, quantifying player/user behaviour – into non-game domains, such as work, productivity and fitness. Such practices are deeply problematic as they represent the capture of ‘play’ in the pursuit of neoliberal rationalization and the managerial optimization of working life and labour. However, applying games and play to social life is also central to the Situationist International, as a form of resistance against the regularity and standardization of everyday behaviour. In this article, the authors distinguish between two types of gamification: first, ‘gamification-from-above’, involving the optimization and rationalizing of work practices by management; and second, ‘gamification-from-below’, a form of active resistance against control at work. Drawing on Autonomism and Situationism, the authors argue that it is possible to transform non-games into games as resistance, rather than transferring game elements out of playful contexts and into managerial ones. Since the original ‘gamification’ term is now lost, the authors develop the alternative conception as a practice that supports workers, rather than one used to adapt behaviour to capital. The article concludes with a renewed call for this ‘gamification-from-below’, which is an ideal form of resistance against gamification-from-above and its capture of play in pursuit of work.